Diversity- Oriented Synthesis of 2, 5- diketopiperazines via Ugi/6- Exo- Trig Aza-Michael Reaction Cascades in One Pot. (October 2019) - Shang, Tianyi; Pan, Yan; Chen, Zhong; Yang, Junjie; Guo, Xinling; Guo, Leilei; Liu, Yan
Abstract: Diversity-oriented synthesis of 2, 5-diketopiperazines was accomplished via Ugi/aza-Michael reaction cascades in one pot. The intramolecular hydrogen bonding between the heteroatom (O or N) from the aldehyde component and the amide -NH group facilities the aza-Michael transformation. This protocol offers a straightforward and concise method to build diversified 2, 5-diketopiperazines library for drug discovery.